2020
DOI: 10.3389/fphys.2020.00927
|View full text |Cite
|
Sign up to set email alerts
|

A Guard Cell Abscisic Acid (ABA) Network Model That Captures the Stomatal Resting State

Abstract: Stomatal pores play a central role in the control of carbon assimilation and plant water status. The guard cell pair that borders each pore integrates information from environmental and endogenous signals and accordingly swells or deflates, thereby increasing or decreasing the stomatal aperture. Prior research shows that there is a complex cellular network underlying this process. We have previously constructed a signal transduction network and a Boolean dynamic model describing stomatal closure in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
(129 reference statements)
1
15
0
Order By: Relevance
“…The impact of the successive activation of K + efflux channels and the H + -ATPase on the GtACR1-induced depolarization was studied with a mathematical model. Models for guard cells responses have been published earlier (48,49), but these models were based on holistic approaches and therefore not suitable for our purpose. We developed the minimal GuardIon model (Fig.…”
Section: Prolonged Gtacr1 Stimulation Activates Guard Cell K + Efflux Channels and H + Pumpsmentioning
confidence: 99%
“…The impact of the successive activation of K + efflux channels and the H + -ATPase on the GtACR1-induced depolarization was studied with a mathematical model. Models for guard cells responses have been published earlier (48,49), but these models were based on holistic approaches and therefore not suitable for our purpose. We developed the minimal GuardIon model (Fig.…”
Section: Prolonged Gtacr1 Stimulation Activates Guard Cell K + Efflux Channels and H + Pumpsmentioning
confidence: 99%
“…A large number of studies reported that ABA maintains water levels in the cell as it controls stomatal activity [38]. In general, low water retention allows guard cells around stomata to close and, at higher moisture levels, it activates the stomatal conductance and stimulates the transpiration rate [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the SNP associated with P WQ (JAR13490) was found in the chromatin-remodelling factor PKL gene that has been consistently linked to multiple plant development processes, particularly to the abscisic acid (ABA) pathway regulation (Perruc et al, 2007). ABA is a phytohormone that is well known for controlling stomatal closure (Rajab et al, 2019, Maheshwari et al, 2020, thus being crucial for efficient drought response (Yu et al, 2019, Zhang et al, 2020b. From P MA , one SNP (JAR01263) was found associated with the methionine gamma-lyase (MGL) gene.…”
Section: Adaptation To Temperature and Precipitationmentioning
confidence: 99%